2000
DOI: 10.1097/00000478-200003000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Histopathologic Changes in Gastroesophageal Reflux Disease

Abstract: A series of 71 patients with multiple measured biopsies of the gastroesophageal junctional region permitting assessment of the presence and length of different glandular epithelial types is presented. All but nine of 53 patients in whom a 24-hour pH study was performed had abnormal reflux, suggesting that endoscopic recognition of an abnormal columnar mucosa at the gastroesophageal junction sufficient to precipitate multiple-level biopsies indicates a high probability of abnormal reflux. All patients had cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
118
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 19 publications
4
118
2
Order By: Relevance
“…Because the incidence and extent of the cardiac glands were linked to excessive gastroesophageal reflux, this led Chandrosoma et al [9] to speculate that cardiac glands may be an acquired change from esophageal squamous mucosa. However, cardiac glands were subsequently identified in most children, the newborn, and even in fetuses [10][11][12], suggesting that they are present from early in life, representing a functionally distinct, albeit small, anatomical region of the normal stomach.…”
Section: The Gastric Cardia and Gca: Anatomy And Definitional Issuesmentioning
confidence: 99%
“…Because the incidence and extent of the cardiac glands were linked to excessive gastroesophageal reflux, this led Chandrosoma et al [9] to speculate that cardiac glands may be an acquired change from esophageal squamous mucosa. However, cardiac glands were subsequently identified in most children, the newborn, and even in fetuses [10][11][12], suggesting that they are present from early in life, representing a functionally distinct, albeit small, anatomical region of the normal stomach.…”
Section: The Gastric Cardia and Gca: Anatomy And Definitional Issuesmentioning
confidence: 99%
“…Several studies have also shown that the length of mucosa composed of mucous glands at the GEJ region increases with more severe degrees of GERD (17,24,28,33,34). Chandrasoma et al postulated that expansion of the zone of mucosa at the GEJ composed of pure mucous glands occurs exclusively as a result of GERD-induced squamous to columnar metaplasia of the distal esophagus (34).…”
Section: Histopathology Of the Distal Esophagusmentioning
confidence: 99%
“…Chandrasoma et al postulated that expansion of the zone of mucosa at the GEJ composed of pure mucous glands occurs exclusively as a result of GERD-induced squamous to columnar metaplasia of the distal esophagus (34). Although it is well-known that GERD increases in prevalence with age, it is unclear whether small amounts of GERD may be "physiologic" in some individuals.…”
Section: Histopathology Of the Distal Esophagusmentioning
confidence: 99%
“…However, an autopsy study has noted that the presence and extent of cardiac mucosa increases with age (12). The finding of cardiac-type mucosa in the lower esophagus, which does not meet the definition of BE, has been correlated with the presence and severity of gastroesophageal reflux disease (GERD) (13). These studies suggest that cardiactype mucosa may not be a normal finding in either the stomach or esophagus.…”
mentioning
confidence: 99%
“…The etiology of CIM may be different from BE. The main risk factor for BE is GERD (13)(14)(15). Although the presence of Helicobacter pylori infection is linked to CIM (16 -20), in the absence of H. pylori infection CIM may be related to GERD (21).…”
mentioning
confidence: 99%